Psychological predictors of chronic posttraumatic stress disorder after motor vehicle accidents. - Ehlers, A; Mayou, R; Bryant, B (1998)
A prospective longitudinal study assessed 967 consecutive patients who attended an emergency clinic shortly after a motor vehicle accident, again at 3 months, and at 1 year. The prevalence of posttraumatic stress disorder (PTSD) was 23.1% at 3 months and 16.5% at 1 year. Chronic PTSD was related to some objective measures of trauma severity, perceived threat, and dissociation during the accident, to female gender, to previous emotional problems, and to litigation. Maintaining psychological factors, that is, negative interpretation of intrusions, rumination, thought suppression, and anger cognitions, enhanced the accuracy of the prediction. Negative interpretation of intrusions, persistent medical problems, and rumination at 3 months were the most important predictors of PTSD symptoms at 1 year. Rumination, anger cognitions, injury severity, and prior emotional problems identified cases of delayed onset.